DESIGN AN AUTOMATIC BELL BASED ON ARDUINO UNO AT STATE VOCATIONAL SCHOOL 5 SERANG CITY - Mabruri, Ali; Rufa’I , Ahmad; Saputra , Memed (Komunitas Menulis dan Meneliti (Kolibi), 2024)
School bells that use electricity produce a buzzer sound or a series of tones on the bell machine that change every time during class, recess or after school. By utilizing Arduino microcontroller technology, the school bell can automatically start ringing according to the clock settings. With this technology, school bells can be controlled at certain times according to a schedule and turn on automatically. With an Arduino-based sound output, all the information produced can be easily understood. This research uses the SDLC (System Development Life Cycle) method, which is a general methodology in system development that marks the progress of analysis and design efforts by dividing 2 types of systems, namely hardware systems and software systems. because the electronic system (hardware) is able to provide automatic notification sound output with economical electricity consumption and a sound frequency that is clearly audible when tested according to the time of teaching and learning activities at school. Makes it easier to ring/activate the school bell, because the school bell is automatically included in the school bell. So the school bell rings automatically according to the schedule that has been entered (software).